2019
DOI: 10.3835/plantgenome2018.08.0061
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Gene‐Centric Approach to Define Haplotypes and Identify Alleles on the Basis of Dense Single Nucleotide Polymorphism Datasets

Abstract: core ideas • A gene-centric approach for haplotype definition was developed and implemented in R. • The tool allows for allelic characterization at given loci in germplasm collections. • Allelic status at four maturity genes is predicted on the basis of marker genotyping data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…HaplotypeMiner (Tardivel et al. unpublished) and the GmHapMap SNP dataset were used to identify 405,101 gene-centric haplotypes (GCHs) for 52,823 genes (94.5% of all soybean genes (55,589)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HaplotypeMiner (Tardivel et al. unpublished) and the GmHapMap SNP dataset were used to identify 405,101 gene-centric haplotypes (GCHs) for 52,823 genes (94.5% of all soybean genes (55,589)).…”
Section: Resultsmentioning
confidence: 99%
“…This is the first time that a comprehensive description of GCHs, for the complete set of genes (55,589), has been achieved for a species. This catalogue of GCHs was obtained using HaplotypeMiner (Tardivel et al. unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many tools exist to visualize haplotypes in a region of interest (e.g., Haploview; Barrett et al 2005), we have found it difficult to rely on such tools alone to define, in a rational and systematic way, the set or subset of SNPs that accurately capture haplotype diversity, and possibly the underlying alleles. The HaplotypeMiner tool (Tardivel et al 2019) exploits information on the linkage disequilibrium between SNPs to capture an informative subset of SNPs lying to either side of a gene of interest. Even using data from simple genome scans (GBS, SNP array), it was possible to screen a collection of Canadian soybean accessions and to identify not only known alleles at key genes controlling maturity, but also to identify novel alleles based on unique haplotypes that did not match those of previously characterized alleles (Tardivel et al 2014(Tardivel et al , 2019.…”
Section: New Opportunity To More Rationally Explore Pgrsmentioning
confidence: 99%
“…The HaplotypeMiner tool (Tardivel et al 2019) exploits information on the linkage disequilibrium between SNPs to capture an informative subset of SNPs lying to either side of a gene of interest. Even using data from simple genome scans (GBS, SNP array), it was possible to screen a collection of Canadian soybean accessions and to identify not only known alleles at key genes controlling maturity, but also to identify novel alleles based on unique haplotypes that did not match those of previously characterized alleles (Tardivel et al 2014(Tardivel et al , 2019.…”
Section: New Opportunity To More Rationally Explore Pgrsmentioning
confidence: 99%